Micro-Video Problem-Based Learning in English Subjects for Grade II Elementary School - Mirayanti, Ni Made; I Komang Sudarma; I Kadek Suartama (Universitas Pendidikan Ganesha, 2025)
Foreign languages are important communication tools in the era of globalization. One that gets special attention is English, especially for students in Elementary Schools so that they can start early. However, the reality in the field shows that second grade elementary school students tend to feel bored and confused due to the lack of use of interesting media in their learning process. This study aims to analyze the design of micro video development in English subjects. This research is a development research and uses the ADDIE development model. The subjects involved in this study were three experts and second grade students Elementary School. Data collection in the study was carried out using observation, interviews, document recording, and questionnaires. The data analysis used was quantitative descriptive and qualitative descriptive analysis techniques. The study showed that micro videos were consistently rated as very good by content experts (88.45%), media experts (94.54%), design experts (95.81%), individual tests (93.66%), small group tests (91.78%), and field tests (95.38%). Based on these results, it can be concluded that micro video innovation is effective to be developed and taught to grade II elementary school students, especially to improve students' communication skills and English learning outcomes. This study has implications in the field of education because it can improve students' understanding and involvement, as well as develop critical thinking skills from an early age.